2018
DOI: 10.3389/fnins.2018.00209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gene-Based Family-Based Methods to Detect Novel Genes Associated With Familial Late Onset Alzheimer Disease

Abstract: Gene-based tests to study the combined effect of rare variants on a particular phenotype have been widely developed for case-control studies, but their evolution and adaptation for family-based studies, especially studies of complex incomplete families, has been slower. In this study, we have performed a practical examination of all the latest gene-based methods available for family-based study designs using both simulated and real datasets. We examined the performance of several collapsing, variance-component… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…However, in a study on AD patients and controls, very few differentially expressed genes between male and female microglia other than gonosomal genes were found 70 . Other differentially expressed genes with sex include more HIF3A in female OPCs (related to oxidative stress) (Figure 7f), more NRXN1 in female oligodendrocytes (Figure 7g), more LAMA2 in female astrocytes (related to the BBB) (Figure 7h), and more pro-inflammatory genes such as HLA-DRB5 and IFI44L in female microglia (Figure 7i), with more CPAMD8 (associated with late-onset Alzheimer’s disease 71 ) in male astrocytes, (Figure 7h), and higher expression of DUSP1 which modulates microglia towards a homeostatic phenotype 72 in male microglia (Figure 7i). These changes suggest sex differences in the link between inflammation and ageing, and may explain some sex dimorphism in neurodegenerative disease susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…However, in a study on AD patients and controls, very few differentially expressed genes between male and female microglia other than gonosomal genes were found 70 . Other differentially expressed genes with sex include more HIF3A in female OPCs (related to oxidative stress) (Figure 7f), more NRXN1 in female oligodendrocytes (Figure 7g), more LAMA2 in female astrocytes (related to the BBB) (Figure 7h), and more pro-inflammatory genes such as HLA-DRB5 and IFI44L in female microglia (Figure 7i), with more CPAMD8 (associated with late-onset Alzheimer’s disease 71 ) in male astrocytes, (Figure 7h), and higher expression of DUSP1 which modulates microglia towards a homeostatic phenotype 72 in male microglia (Figure 7i). These changes suggest sex differences in the link between inflammation and ageing, and may explain some sex dimorphism in neurodegenerative disease susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed whole exome and whole genome sequence data from three cohorts: a familial late onset AD (FASe, 525 families, cases=1,212, controls=341) (Fernández et al, 2017(Fernández et al, , 2016(Fernández et al, , 2018, an early onset AD (EOAD,cases=1,385,controls=3,864), whose data was generated at Washington University in St. Louis (WASHU) (Fernández et al, 2016(Fernández et al, , 2018, and a case-control late onset AD (LOAD) from the ADSP (ADSP, cases=5,679, controls=4,601) (Beecham et al, 2017). The ADSP data (pht003392.v7.p4) is available to qualified researchers through the database of Genotypes and Phenotypes (https://www.ncbi.nlm.nih.gov/projects/gap/cgibin/dataset.cgi?study_id=phs000572.v8.p4&pht=3392).…”
Section: Methodsmentioning
confidence: 99%
“…The ADSP data (pht003392.v7.p4) is available to qualified researchers through the database of Genotypes and Phenotypes (https://www.ncbi.nlm.nih.gov/projects/gap/cgibin/dataset.cgi?study_id=phs000572.v8.p4&pht=3392). The WASHU datasets were processed (alignment to GRCh37, variant calling, quality control and annotation) as previously described (Fernández et al, 2017(Fernández et al, , 2018. Cryptic relatedness (IBD analysis) and population admixture (PCA analysis) were performed in each of the datasets using PLINK 1.9 and only non-Hispanic whites were kept for further analyses (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found that several variants in NLRP9 may influence the disease course in multiple sclerosis patients, as determined by an exome sequencing study [19], and may be associated with familial late-onset Alzheimer's disease, as determined by a genome-wide association study [20]. However, little has been found regarding its effects on litter size.…”
Section: Association Analyses Of Nlrp5 and Nlrp9mentioning
confidence: 99%